2002
DOI: 10.1007/bf02967581
|View full text |Cite
|
Sign up to set email alerts
|

Breast-conserving therapy versus modified radical mastectomy in the treatment of early breast cancer in Japan

Abstract: Breast-conserving therapy is comparable to modified radical mastectomy in overall survival and disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the last couple of decades it has been demonstrated by various studies (Fisher et al 2002, Veronesi et al 2002, Horiguchi et al 2002, van Dongen et al 2000, Early Breast Cancer Trialists' Collaborative Group 1995 that the treatment of early-stage breast cancer with BCS plus radiotherapy yields equivalent results to mastectomy. As early detection increases, more cancers are diagnosed in the early stage and BCS treatments play a central role in the management of breast cancer.…”
Section: Comparison Of Multi-institutional and Multi-mode Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last couple of decades it has been demonstrated by various studies (Fisher et al 2002, Veronesi et al 2002, Horiguchi et al 2002, van Dongen et al 2000, Early Breast Cancer Trialists' Collaborative Group 1995 that the treatment of early-stage breast cancer with BCS plus radiotherapy yields equivalent results to mastectomy. As early detection increases, more cancers are diagnosed in the early stage and BCS treatments play a central role in the management of breast cancer.…”
Section: Comparison Of Multi-institutional and Multi-mode Radiotherapymentioning
confidence: 99%
“…Breast cancer is the most common cancer in women. In the last two decades it has been demonstrated by various randomized studies that the treatment of early-stage breast cancer with BCS plus radiotherapy yields an equivalent outcome to mastectomy (Fisher et al 2002, Veronesi et al 2002, Horiguchi et al 2002 van Dongen et al 2000, Early Breast Cancer Trialists' Collaborative Group 1995. Typically, after conservative surgery, the entire breast is treated with photon EBRT of 45-50 Gy in 1.8-2 Gy fractions over 5 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The downside of diagnostic criteria chosen to maintain high sensitivity is possible overstaging. If pretreatment MRI characterizes associated benign disease as multifocal lobular cancer, the use of MRI will result in a certain number of unnecessary mastectomies without a demonstrated benefit in increased survival (37). Therefore, diagnostic criteria for staging and assessing the extent of known breast cancer should optimize specificity.…”
Section: Tumor‐related Factorsmentioning
confidence: 99%
“…During a median follow-up duration of 78 months, Sakurai et al reported a cancer recurrence rate at the NAC of 3.7% among 788 patients who underwent NSM without radiotherapy between 1985 and 2004. A few other series on NSM that reported follow-up durations of at least 5 years involved patients treated in the 1980s and/or 1990s, when the adjuvant systemic therapy and radiation therapy regimens currently used in clinics had not yet been established as the criterion standard. In our study, we included only patients with invasive breast cancer who underwent NSM and immediate breast reconstruction between 2003 and 2015 and identified a low 5-year cumulative incidence of cancer recurrence at the NAC of 3.5%, which we believe was acceptable given the study population in the current series and the relatively long follow-up period.…”
Section: Discussionmentioning
confidence: 99%